Effect of oral contraceptive use on the incidence of dry socket in females following impacted mandibular third molar extraction: a meta-analysis. Issue 9 (September 2015) - Xu, J.-L.; Sun, L.; Liu, C.; Sun, Z.-H.; Min, X.; Xia, R.
Abstract The aim of this comprehensive meta-analysis was to provide evidence-based data to test whether oral contraceptive (OC) use can promote the incidence of dry socket (DS) in females following impacted mandibular third molar extraction. PubMed, the Cochrane Library, and Elsevier Science Direct databases were searched. The pooled risk ratio (RR) with 95% confidence interval (CI) was calculated using fixed-effects or random-effects model analysis. Heterogeneity among studies was evaluated with the Cochran test and I2 statistic. Study quality was assessed with the Newcastle–Ottawa scale. Of 70 articles identified in the search, 12 reporting 16 clinical controlled trials were included in this study. The incidence of DS was significantly greater in the OC groups than in the control groups (RR 1.80, 95% CI 1.33–2.43). Subgroup analyses showed that the unit assessed (tooth or patient), the region in which the study was conducted, and the intervention were not related to the incidence of DS in females taking OC after impacted mandibular third molar extraction. The sensitivity analysis showed no significant change when any one study was excluded. Publication bias was also not detected. This study suggests that OC use may promote the incidence of DS in females following impacted mandibular third molar extraction.